Effects of human chorionic gonadotropin and intravaginal progesterone device treatment after artificial inseminations on the reproductive performance of normal and repeat breeder lactating dairy cows - IZUMI, Taiki (J Reprod Dev, 2020)
We examined the effects of human chorionic gonadotropin (hCG) treatment on Day 5 (Day 0 = day of artificial insemination: AI) and intravaginal progesterone device (IVPD) treatment from Day 5 to 19 on the conception and detection rates of return to estrus (re-estrus) in lactating dairy cows. A total of 306 cows from a commercial dairy farm were divided into the following three groups on Day 5: non-treatment group (n = 128), untreated; hCG group (n = 71), 3,000 IU hCG was administered (intramuscularly); IVPD group (n = 107), IVPD was inserted into the vagina from Day 5 to 19. Re-estrus detection was performed up to Day 25. Pregnancy was diagnosed by rectal palpation between Day 50 and 60. There was an interaction between treatment and AI number (P < 0.01) on the conception rate of first-AI. For cows with more than three AIs, the IVPD treatment (66.7%) was more effective than the non-treatment (23.1%) (P < 0.05). The re-estrus detection rate was significantly (P < 0.05) higher in the IVPD group (60.7%) than that in the non-treatment group (41.4%) and tended (P < 0.1) to be higher than that in the hCG group (37.8%). Our results suggested that the conception rate can be improved by IVPD treatment, especially in cows with more than three AIs. In addition, IVPD treatment can induce higher estrus expression up to 25 days after AI in non-pregnant cows.